Decision Support System for Selection of Suitable Mariculture Site in the Western Part of Java Sea, Indonesia - Windupranata, W.; Mayerle, R. (Journal of Engineering and Technological Sciences, 2009)
Mariculture (marine aquaculture) has been intensified and has created essentialÂ  employmentÂ  opportunitiesÂ  overÂ  theÂ  lastÂ  two-decadesÂ  inÂ  Indonesia,Â  as well as many other countries in the world. This development has negative impact toÂ  theÂ  environment.Â  ConsiderableÂ  amountsÂ  ofÂ  nutrientÂ  wasteÂ  inÂ  dissolvedÂ  and particulateÂ  formÂ  wereÂ  releasedÂ  byÂ  intensiveÂ  fishÂ  farmingÂ  intoÂ  theÂ  environment throughÂ  feedÂ  excess,Â  solubleÂ  fishÂ  excretionÂ  andÂ  faecesÂ  production.Â  OneÂ  ofÂ  the first steps toÂ  avoid the dangerous environmental impacts is careful site selection toÂ  minimizeÂ  environmentalÂ  impactsÂ  arisingÂ  fromÂ  theÂ  farmingÂ  activities (sustainability) as well as to guarantee adequate conditions from the operational point of view (suitability).The paper focuses on the development of a Decision Support SystemÂ  (DSS) as a tool for the appropriate selection of maricultureÂ Â  site location. The DSS is based onÂ  physical,Â  chemicalÂ  andÂ  sedimentÂ  criteriaÂ  asÂ  wellÂ  asÂ  onÂ  dataÂ  ofÂ  conflicting coastal use. The GIS analysis results in a map indicating the suitable areas for the improvedÂ  methodÂ  ofÂ  offshoreÂ  cageÂ  mariculture.Â  InÂ  thisÂ  study,Â  emphasisÂ  was placed on finfish species; however the methods and results may be employed for other species as well following some modifications.The DSS was applied for theÂ  western part of Java Sea, Indonesia. The data were acquiredÂ  fromÂ  directÂ  fieldÂ  measurement,Â  numericalÂ  modelingÂ  andÂ  existing informationÂ  fromÂ  particularÂ  agencies.Â  NumericalÂ  modelingÂ  wasÂ  usedÂ  toÂ  obtain spatialÂ  andÂ  temporalÂ  distributionsÂ  ofÂ  hydrodynamicÂ  parametersÂ  (i.e.Â  current velocitiesÂ  andÂ  waterÂ  levels).Â  TheÂ  Delft3DÂ  modelingÂ  systemÂ  (DelftÂ  Hydraulics, The Netherlands) was employed for this purpose. The DSS was developed under GISÂ  applicationÂ  ofÂ  ESRIÂ®Â  ArcGISâ¢Â  usingÂ  weightedÂ  overlayÂ  method.Â  The resultsÂ  showedÂ  theÂ  adequacyÂ  ofÂ  theÂ  systemÂ  forÂ  supportingÂ  governmental authorities in the implementation, environmental controlling, and estimationÂ  of overall carrying capacity for environmental sustainable marine fish farming.